PENGARUH CAPACITY, CAPITAL DAN COLLATERAL TERHADAP TINGKAT PENGEMBALIAN ANGSURAN KREDIT PADA PD. BANK PERKREDITAN RAKYAT (BPR) NUSA TENGGARA BARAT SUMBAWA - U Usman; Rosyidah Rachman; Diah Fidayanti (Jurnal Ekonomi & Bisnis, 2022)
This study aims to analyze the effect of capacity, capital and collateral toward the rate of return on installments of financing in PD. BPR NTB Sumbawa. The data used in this study was primary data. The numbers of sample were 27. Technique used to determine sample was non-reliability sampling. The methods of analysis in this study were validity test, reliability of the data, data normality test, autocorrelation test. multicollinearity test, heteroscedasticity test, multiple linear regression test, hypothesis test and test the coefficient of determination (R2). The results of the multiple linear regression test showed that the variable capacity had a positive effect toward the rate of repayment of financing installments with a capacity coefficient of 0.413, the variable capital had a positive effect toward the rate of return on financing installments with a capacity coefficient of 0.533. Collateral variable had a positive effect toward the repayment rate of financing installments with a collateral coefficient of 0.225. The results of the t test of this study indicate that the variable capacity has a significant effect on 0.01<0.05. The variable capacity was significant of 0.01<0.05. Collateral variable was not significant 0.102>0.05. The results of the F test of the Capacity, Capital, and Collateral variables simultaneously had a significant effect toward the repayment rate financing installments in PD. BPR NTB SUMBAWA with a significant level of 0.000<0.05. The coefficient of determination was found in the R square value of 0.792, the independent variable in explaining the dependent variable was 79.2%.